Examining the Impact of Phubbing Behaviors on Toxic Disinhibition in Online Social Interactions - vivi sumanti; Afdal Afdal (Universitas Ahmad Dahlan, 2023)
The study has two main objectives: firstly, to examine the relationship between phubbing and toxic disinhibition; secondly, to compare the levels of phubbing and toxic disinhibition based on gender and place of residence. This research adopts a cross-sectional design with a quantitative approach. The study employs a incidental sampling technique to collect data from 896 Indonesian college students across various provinces, including West Sumatra, Bali, Banten, Bengkulu, DKI Jakarta, DI Yogyakarta, Jambi, West Java, Central Java, East Java, South Kalimantan, West Kalimantan, Central Kalimantan, East Kalimantan, Riau Islands, Nanggroe Aceh, Papua, East Nusa Tenggara, Riau, West Sulawesi, North Sulawesi, South Sulawesi, and North Sumatra. Data analysis involves regression analysis and one-way ANOVA. The research findings reveal that 1) toxic disinhibition behavior is relatively common among Indonesian college students (59%), 2) phubbing behavior is also quite prevalent (69%), and 3) there is a significant correlation between phubbing and toxic disinhibition. 4) There is a significant difference in the level of toxic disinhibition between males and females, 5) there is a significant difference in the level of phubbing between participants residing in urban areas and those in suburban areas. The implications of this study emphasize the need to control phubbing behavior in order to reduce toxic disinhibition behavior among college students. A proactive counseling approach can be applied by counselors to address the issues of phubbing and toxic disinhibition.